Pemanfaatan Cerita Rakyat sebagai Media Penguatan Literasi Bahasa Indonesia - Maria Florida Ferando; Yeremias Bardi; Yohanes Kristianus Firman Raja Mayeli; Maria Mea Rada; Maria Risanti Mude; Paulinus Ngasu Penu Selviana Du’a Bolor (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
Socializing and improving literacy movement skills in schools have not yielded maximum results because of the low level of mentoring and training to improve literacy awareness and skills among students and teachers. Many teachers still assume that literacy is the responsibility of Indonesian language subject teachers. In addition, reading materials and texts available in schools have not been optimally utilized to develop students' literacy skills. The purpose of this study was to determine the use of folklore as a medium for strengthening Indonesian language literacy in the world of education. This study used a library research method to analyze the use of folklore as a medium for strengthening Indonesian language literacy. The results of the study showed that folklore has great potential in strengthening Indonesian language literacy. Folklore not only functions as an entertaining medium, but also as an effective learning tool to develop students' reading and writing skills. Through folklore, students can enrich their vocabulary, understand text structures, and improve their understanding of good and correct Indonesian. In addition, folklore also teaches moral, social, and cultural values ​​that are very relevant to students' daily lives. By introducing values ​​such as honesty, hard work, and respect for parents, folklore can educate students to have a good attitude in their lives. Folklore also plays an important role in introducing and preserving local culture, strengthening the nation's cultural identity, and increasing pride in Indonesia's cultural heritage.